أساليب سن الدساتير العراقية الصادرة من سنة 1925-2005 - د. سحر محمد نجيب (PROSPECTIVE RESEARCHES, 2023)
This research aims at showing the ways and the methods which were followed in preparing and legislating Iraqi constitutions though the period between (1925 - 2005). These constitutions used to differ according to the different conditions and circumstances which accompanied the legislation of each constitution. The content of each constitution reflects the conditions and the circumstances of its time, especially the conditions which depend on the type of the government system and the status of the political and social development of the people, in addition to the legal conceptual framework of the people which is considered a main element in legislating the constitutions because it represents the principle of the public dominance which ,in its turn, represents the basis of the modern democratic political systems. This research sheds light on the importance of preserving the needs of the public in legislating the constitution. It is very important to avoid depending on exceptional circumstances as a mean of imposing hasty constitutions which do not represent the need and the ambitions of the people.